The Effect of Funding Liquidity on Risk Taking Behaviour of Conventional Banks - Susy Muchtar, Nur Mariana Samosir (Jurnal Manajemen, 2020)
This Research aims to determine the effect of funding liquidity on risk taking behaviour. Sample used was 36 conventional banks listed on Indonesia Stock Exchange in the period 2014-2018. The sampling technique used was purposive sampling and the method analysis was panel data regression. The independent variable are funding liquidity measured by deposits, loan and size, and the control variable are gross domestic product, interest rate and unemployee, and the dependent variable are risk taking behavior. The results showed that deposits and loan has negative effect on risk taking behavior. Size, gross domestic product, interest rate and unemployee has no effect on risk taking behavior. The results of this research are expected to be the reference for companies to see the factors that influence risk taking behavior.